Identifikasi dan Pengelolaan Risiko Rantai Pasok Rumah Produksi Tahu Apu dengan Metode House of Risk - Abrori, Farid, Indah Pratiwi, ST., MT (2017)
Rumah Produksi Tahu APU is one of the industry tahu who is in Dukuh Girirejo, Jemawan Village, Jatinom District, Klaten Regency. According to the observations that have been made there are not maximum coordination on supply chain flow. Uncertainty of the types of risks that may occur in any activity undertaken will hamper the production process and have an impact on the operational and financial losses. The purpose of this study is to identify risk events that arise, determine the causes of risk should be prioritized, and determines the risk management strategy to address the causes of risk in the supply chain Rumah Produksi Tahu APU. The benefits of this research is to provide information about the causes of management strategies to reduce the risk and minimize the impact of such risks. Risk management can be accomplished by using the House of Risk (HOR) is divided into two stages: stage risk identification (HOR phase 1) and the formulation of risk management strategies (HOR phase 2). Based on the HOR phase 1 activity mapping identified a total of 23 Risk Event and 25 Risk Agent. Through analysis using FMEA concept as much as 7 causes the dominant risk is known value of the Aggregate Risk Potential (ARP). HOR Phase 2 the formulation of risk management strategies and formulation of strategy successfully designing a number of 14 formulation of strategies.